2015
DOI: 10.1158/2159-8290.cd-14-1507
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α-Dependent Lipid Storage Promotes Endoplasmic Reticulum Homeostasis in Clear-Cell Renal Cell Carcinoma

Abstract: Two hallmarks of clear cell renal cell carcinoma (ccRCC) are constitutive hypoxia inducible factor (HIF) signaling and abundant intracellular lipid droplets (LDs). However, regulation of lipid storage and its role in ccRCC are incompletely understood. Transcriptional profiling of primary ccRCC samples revealed that expression of the LD coat protein gene PLIN2 was elevated in tumors and correlated with HIF-2α, but not HIF-1α, activation. HIF-2α dependent PLIN2 expression promoted lipid storage, proliferation, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
343
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(357 citation statements)
references
References 51 publications
(92 reference statements)
12
343
1
1
Order By: Relevance
“…We found extensive enhancer gains around well-characterized hypoxia-related targets (ref. 95 51,99). New targets revealed in this study include SMPDL3A, which could be another important ccRCC-specific oncogene given its role in lipid and cholesterol metabolism (61,100).…”
Section: Discussionmentioning
confidence: 88%
“…We found extensive enhancer gains around well-characterized hypoxia-related targets (ref. 95 51,99). New targets revealed in this study include SMPDL3A, which could be another important ccRCC-specific oncogene given its role in lipid and cholesterol metabolism (61,100).…”
Section: Discussionmentioning
confidence: 88%
“…Our results also extend an emerging theme in which oncogenic transformation simultaneously induces anabolic metabolism to increase proliferation along with homeostatic pathways that maintain cell viability. These include lipid and protein scavenging in RAS-transformed tumors (39,53), autophagy downstream of c-Myc overexpression (10), and lipid storage downstream of HIF2α activation (54). The role of the IRE1α/XBP1 pathway in human cancers may be more general, as Genovese et al recently demonstrated that pancreatic ductal adenocarcinoma cells exhibiting a Myc geneexpression signature undergo an anabolic switch that increases protein metabolism and adaptive activation of IRE1α-mediated survival pathways (55).…”
Section: Discussionmentioning
confidence: 99%
“…LDs are also shown to be associated with viral assembly of hepatitis C virus (HCV), dengue virus, bacterial infection, and anti-pathogen infection due to its association with Histone proteins and Viperin (Anand et al, 2012;Camus et al, 2013;Crawford and Desselberger, 2016;D'Avila et al, 2008;Filipe and McLauchlan, 2015;Hinson and Cresswell, 2009). Most recent research has demonstrated that the size of LDs and increased lipid accumulation is associated with cancer development and neural degenerative diseases (Baenke et al, 2013;Chen and Li, 2016;Liu et al, 2015;Qiu et al, 2015).…”
Section: The Structure and Function Of Ldsmentioning
confidence: 99%